Legendagem e o processo tradutório : uma abordagem discursivo-desconstrucionista da tradução para legendas do documentário "Lixo extraordinário" - Boito, Fernanda Silveira (2013)
The deconstruction perspective questions many concepts traditionally related to translation, such as potential essentiality of original texts and the possibility of retrieving determined and steady meanings from them. Thus, postmodernism does not conceive translation as a transfer mechanism, in which meaning is transmitted from one language to another, but as a process in which meaning is built and correlated, a re-enunciation, and a new text. From this point ofview, translation is construed as an interpretative activity, strongly associated with historical, social, cultural and ideological issues, in which meaning is produced by a translator who is a reader situated at a specific time and place. Hence, this research aimed at analyzing the English subtitles of the documentary Waste Land (translated into Brazilian Portuguese as Lixo Extraordinário) from a discursive-deconstructionist translation point of view. In particular, this study aimed at analyzing whether Brazilian cultural aspects are transmitted, maintained or transformed in the translation process, based on the choices made by the translator; reflecting and discussing whether the translator's choices may influence the identity construction of the picker; and also discussing the inherent ideological aspects in the translation process. This thesis is based on the need of producing a research that may contribute to the Translation Studies field, within the scope of Discourse Analysis, focusing on the translation process of subtitles, adding information as well as deepening the studies on this kind of translation that has certainly expanded. Our analyses corroborate the post-modern claims that cultural and ideological aspects are inherent in the translation process, considered as a new text of which meanings are produced within a series of relations established among them and where the translator?s voice is always present. Moreover, our analyses show that the translator?s choices are able to produce effects of meaning which may be different from those produced by the source text, including effects of identity. These findings lead us to conceive translation as a socially active instrument, capable of transforming cultures and (re) building identities.